Synthesis and thermal properties of soluble silicon containing phenylated aromatic-aliphatic polyamides - Ghanwat, A. A.; Sayyed, M. M.; Wadgaonkar, P. P.; Maldar, Noormahamad N. (Journal of Thermal Analysis and Calorimetry, 2009)
Aromatic polyamides find many applications in diverse and critical areas due to their high thermal stability coupled with high mechanical properties. However most of such aramides are difficult to fabricate because of their limited solubility and high melting temperature. Improvements in processability have been reported by incorporating bulky pendant groups and aliphatic spacer groups. Similarly to improve the solubility of polymers approaches of incorporating silicon in main polymer chain and co-polymerization techniques were useful. We report the synthesis and characterization of a series of phenylated silicon containing aromatic-aliphatic polyamides from a mixture of 2, 5-bis (4-carboxy methylene phenyl)-3, 4-diphenyl thiophene (CMPDT) and bis-(4-carboxy phenyl) dimethyl silane (BCPDS) in various mole proportions, with commercial aromatic diamine. Thus a series of novel co-polyamides having pendant phenyl groups, methylene spacer and silicon moiety was prepared by judicious combination of (CMPDT); BCPDS and aromatic diamine; bis-(4-aminophenyl) ether (ODA), by direct polycondensation using Yamazaki's phosphorylation method. These high molecular mass polyamides were obtained in high (89-98%) yields and had viscosities in the range of 0.23-0.57 dL/g in DMAc. Polyamides showed improved solubility in polar aprotic solvents, like NMP, DMAc, DMSO and DMF; had high thermal stability; with no mass loss below 335 A degrees C.
Keywords: 2; 4-diphenyl thiophene; 5-bis (4-carboxy methylene phenyl)-3; bis-(4-amino phenyl) ether; bis-(4-carboxy phenyl) dimethyl silane; Copolyamides; solubility; thermal stability

Synthesis and characterization of soluble polyamides from bis-[(4 `-aminobenzyl)-4-benzamide] ether and various diacids - Patil, A. S.; Sayyed, M. M.; Bhairamadgi, Nagendra S.; Han, Sung-Hwan; Maldar, Noormahamad N. (Polymer Bulletin, 2011)
New aromatic diamine containing preformed amide, ether, and methylene; bis-[(4'-aminobenzyl)-4-benzamide] ether (BABE), was synthesized and characterized by FT-IR, NMR, and mass spectrometry. Aromatic-aliphatic polyamides were prepared from BABE with aliphatic/aromatic diacids via Yamazaki's polymerization. The polyamides were characterized by FT-IR, (1)H NMR, inherent viscosity [eta(inh)], solubility tests, differential scanning calorimetry [DSC], thermogravimetric analysis [TGA], and X-ray diffraction [XRD]. Polyamides had inherent viscosities 0.35-0.84 dL/g, soluble in aprotic polar solvents like N-methyl-2-pyrrolidone, N, N-dimethyl acetamide and dimethyl sulphoxide containing LiCl due to an amorphous to partially crystalline morphology; as XRD patterns indicated. DSC analysis of polyamides showed glass transition temperatures 166-268 A degrees C. Polyamides showed high thermal stability as they did not degrade below 300 A degrees C, had 10% weight loss temperature higher than 375 A degrees C, and the char yields at 900 A degrees C were 22-55%; indicating potential applications as engineering materials.
Keywords: Aryl-ether and methylene linkages; Bis-[(4 `-aminobenzyl)-4-benzamide] ether; Direct phosphorylative polycondensation; Soluble aromatic-aliphatic polyamides; Thermal properties